2005
DOI: 10.1021/ac050672d
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Deamidation Sites in the Conserved Regions of Human Immunoglobulin Gamma Antibodies

Abstract: Deamidation of asparagine residues of biological pharmaceuticals is a major cause of chemical degradation if the compounds are not formulated and stored appropriately. The mechanism of this nonenzymatic chemical reaction has been studied in great detail; however, the identification of deamidation sites in a given protein remains a challenge. In this study, we identified and characterized all deamidation sites in the conserved region of a recombinant monoclonal antibody. The conserved region of this antibody is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
234
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(254 citation statements)
references
References 23 publications
20
234
0
Order By: Relevance
“…Ramachandran plot analysis, which is used to calculate peptide φ and ψ angles, revealed that the backbone geometry of HC Asn57 was outside of the theoretically allowed region, which indicated that the structure model around HC Asn57 may have been built incorrectly. 19 As shown in Figure 7A, the backbone carbonyl of HC Asn57 in the original structure model did not match the calculated electron density map. The CDR-H2 loop structure model was refined by flipping the original HC Asn57 backbone carbonyl and then fitting the rest of the loop.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Ramachandran plot analysis, which is used to calculate peptide φ and ψ angles, revealed that the backbone geometry of HC Asn57 was outside of the theoretically allowed region, which indicated that the structure model around HC Asn57 may have been built incorrectly. 19 As shown in Figure 7A, the backbone carbonyl of HC Asn57 in the original structure model did not match the calculated electron density map. The CDR-H2 loop structure model was refined by flipping the original HC Asn57 backbone carbonyl and then fitting the rest of the loop.…”
Section: Resultsmentioning
confidence: 90%
“…These results were consistent with previous reports. 19,20 It should be noted that HC Asn315 is not considered a deamidation hot spot even though up to 8% deamidation was detected in unstressed mAbs because HC Asn315 contains the sensitive NG sequence motif and much of the deamidation detected at this site occurred during peptide map analysis (unpublished observations). Similar method related artifacts were also reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…Modifications, such as N-terminal glutamine and glutamate cyclization [3][4][5][6][7][8][9], different types of the conserved N-linked oligosaccharides [5,[7][8][9][10][11][12][13], amino acid truncation and insertion [8,11], cysteinylation [14], C-terminal lysine processing [5,7,11,15,16], fragmentation [12,15,17], glycation [18], oxidation [19,20], and nitration [21] can be directly determined by measurements of the molecular weights of intact antibodies, antibody light chain and heavy chain, and Fab and Fc fragments after papain or lys-C digestion [14]. On the other hand, analysis at the peptide level is normally required to determine the sites of modifications and modifications with small molecular weight differences, such as deamidation [22,23] and amidation [11], which results in a molecular weight difference of only 1 Da.Mass spectrometry is commonly coupled with reversedphase high-performance liquid chromatography (RP-HPLC), which desalts the samples and separates different components based on hydrophobicity. The molecular weights of intact antibodies [12,15] and their light chains and heavy chains can be readily measured by on-line RP-HPLC and mass spectrometry (MS) [9,24].…”
mentioning
confidence: 99%
“…After administration, the accumulated succinimide hydrolyzes to Asp and/or isoAsp under the physiologic pH. In mAbs, deamidation has been reported in the Fc regions [4,5] and the CDRs [6][7][8][9][10][11][12]. Deamidation in the CDR regions could affect drug efficacy [10,12].…”
Section: In Vivo Mab Modificationsmentioning
confidence: 99%